Flubby does not like snow - Morris, J. E. (Jennifer E.) (2023)
Kami tries to convince her finicky cat, Flubby, to come outside and enjoy the winter wonderland.
Ages 5-7.
Keywords: Cats -- Juvenile fiction; Pets -- Juvenile fiction; Snow -- Juvenile fiction; Winter -- Juvenile fiction; Picture books; Animal fiction; Readers (Publications); Picture books